All Days 2015
DOI: 10.2118/178034-ms
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Acid-Induced Emulsion and Asphaltene Precipitation in Low Permeability Carbonate Reservoirs

Abstract: The increasing demand for energy has extended the development horizon towards relatively tighter formations all over the world. In Saudi Arabia, hydrochloric and organic acids have been extensively used to enhance well productivity or injectivity in low permeability formations. However, the use of these acids was associated with severe formation damage, which is attributed to acid/oil emulsions and/or asphaltene precipitation in some of the low permeability carbonate reservoirs. Consequently, a detailed study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…To simulate the process of oil degassing in the bottom-hole formation zone, pumping of oil at a constant pressure, which is less than saturation pressure of the oil saturated by gas. As a result of this, asphaltenes contained in the oil, will be precipitated mainly within the pore space of the core sample [8,14,17,22,25,27,31,43]. 6.…”
Section: Description and Application Of Equipment And Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…To simulate the process of oil degassing in the bottom-hole formation zone, pumping of oil at a constant pressure, which is less than saturation pressure of the oil saturated by gas. As a result of this, asphaltenes contained in the oil, will be precipitated mainly within the pore space of the core sample [8,14,17,22,25,27,31,43]. 6.…”
Section: Description and Application Of Equipment And Processesmentioning
confidence: 99%
“…For example, the use of various reagents and solvents to remove deposits of asphaltenes, resins and waxes, the application of surfactants, and special physical (e.g. wave) methods on reservoir [6][7][8][9][10]14,16,18,[26][27][28]31,37].…”
Section: Description and Application Of Equipment And Processesmentioning
confidence: 99%
“…However, they ignored the acid-asphaltene reactions, acid-asphaltene sludge formation, and its effects on wormholing process. Similarly, AlMubarak et al [48] investigated the acid-induced emulsion and the precipitation of asphaltene in low permeability reservoir and they found that acid systems are not compatible with several oils when they interact with each other. Furui et al [38] observed a mismatch in predicting wormhole formation during matrix acidizing between theoretically and conventionally developed models as opposed to field data [41].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in this study, the experimental data of the above sources [43][44][45][46][47][48] in the literature were used to propose a model, which considers simultaneous acid-rock and acid-asphaltene reactions as well as acid-asphaltene sludge formation. Furthermore, the effect of several factors on wormholing was investigated in both presence and absence of asphaltene slug formation.…”
Section: Introductionmentioning
confidence: 99%
“…During well interventions involving HCl and when the latter interacts with the formation oil, there may occur asphaltene precipitation in a separate phase with some precipitation of sediments [6,7], which influences the efficiency of oil production and preparation processes.…”
Section: Introductionmentioning
confidence: 99%